Perencanaan Pajak Untuk Usaha Mikro, Kecil, Dan Menengah - Ulfah Fauziah; Bernard E Tidajoh (SUBSTANSI, 2018)
This study aims to propose Tax Planning for MSMEs in Indonesia according to income tax rates criteria on Government Regulation No. 23 of 2018, Article 17 of income tax law and Article 31E of income tax law. At the moment, MSMEs fulfill 99.99% of a total business entity in Indonesia or as much as 56.54 million units. However, the contribution of MSMEs income tax revenue to Indonesia's tax revenues is meager, only at  Rp.5.7 trillion, or equal to 5% of Gross Domestic Product. The theory used in this study is the Hoffman Tax Planning Theory (1961) and the Slippery Slope Framework compliance theory of Kirchler (2007) with mixed method case study approach using primary and secondary data. The result showed that personal MSMEs with net income more than 6% or corporate MSMEs with net income more than 4% were more profitable use the income tax rate in accordance to PP 23 of 2018. Personal MSMEs with net income less than 6% were more profitable use tax rate in accordance to Income Tax Law article 17, as well as corporate MSMEs with net income less than 4% were more profitable use Article 31E rates. Subsequent research is expected to be a draft regulation on new income tax rates that are more in line with taxation principles and the condition of MSMEs in Indonesia.